O psicopata infrator e o ordenamento jurídico-penal brasileiro: uma análise sobre a imputabilidade - Silva, Maelly de Oliveira (Universidade Federal do Tocantins, 2021)
This study aims to discuss the approach given to patients with psychopathy in the Brazilian legal-penal system, focusing on the element of imputability. Initially, it seeks to conceptualize psychopathy and point out the main behavioral and physical changes that pre-existent in the patient, as well as discussing whether there is a possibility of a cure for the problem. Then, the concept of crime is brought up, according to the analytical criteria, examining culpability and comparing it briefly with international law. It also discusses the possibility of applying exclusion from guilt to the figure of the psychopath, bringing an analysis of the imputability of such an individual, observing how it has been treated by Brazilian jurisprudence and the effectiveness of such measures; as well as, exemplifying cases of psychopaths convicted in the country and how the sentence was executed. The research uses the inductive and observational methods, being eminently exploratory and qualitative, with the objectives achieved through bibliographic and documentary research, access to articles, books, magazines, videos and reports that address the issue. In the end, it is possible to assess a possible solution to the problem of the psychopath in the legal system, which in addition to being a legal problem, is social, highlighting the need for greater participation of law and society in order to safeguard basic, collective and individual rights.